Chemotherapy extravasation injuries beyond the immediate stage: A series of 15 cases treated according to a preset surgical algorithm based on time of presentation - Abdel Al, S; Asha, W; Asha, A; Abou Chaar, M.K; Jarrar, A; Qawasmi, M; Salameh, H; Alsaadi, N (Hand surgery and rehabilitation, 2022)
AbstractChemotherapy extravasation can cause severe harm. There is a lack of evidence-based standardization on the surgical management of such injuries beyond the immediate stage. In an algorithm connecting presentation time post-injury with surgical treatment could help standardize future treatment. This study prospectively validated a preset standardized surgical algorithm based on presentation time in a consecutive series between October 2017 and October 2020. Chemotherapeutic agent, site and extent of injury, type of surgery and outcome at a minimum of 6 months’ follow-up were collected. Seven thousand six hundred twelve individuals received chemotherapy during that period; 15 patients suffered extravasation injuries, 2 of whom were referred from outside our hospital. This algorithm distinguished: A) beyond the immediate stage and up to 2 days, treated with saline subcutaneous washout (SCWO) and vacuum-assisted closure (VAC) dressing; B) 2 to 5 days, open surgical decompression and VAC dressing; C) 5 to 10 days, non-operative management with surveillance; and D) more than 10 days, radical necrotic excision with or without VAC dressing and tissue reconstruction. In 2 patients in Group A and 3 patients in Group B, all vesicant symptoms resolved. Five of the 6 patients in Group C (3 vesicant, 3 non-vesicant) did not progress into necrosis or infection, and 1 case of vesicant extravasation progressed to a localized ulcer beyond this period and, as surgery was refused, led to a chronic ulcer with stiffness; 2 cases of non-vesicant extravasation developed a recall phenomenon but resolved after the third cycle. Of the 4 patients in Group D, all vesicant, 2 were treated with no complications, 1 had complex regional pain syndrome (CRPS) due to late presentation, and 1, referred with necrotizing fasciitis, underwent above-elbow amputation but died due to septic shock. This study demonstrated a uniform surgical approach in a series of 15 cases; larger studies are still needed to validate the efficacy of this protocol in reducing morbidity. Level of evidenceIV